Network Optimization of Packaging Water Factory "Aeta" by Using Critical Path Method (CPM) in Tirta Taman Sari Drinking Water Company, Madiun City - Faiz Ainur Razi; Wanda Wira Yudiarti (Jurnal Varian, 2020)
Project management is a new thing with the development of two analytical techniques used for planning, scheduling, and decision making on projects to be carried out so that they can be carried out optimally and efficiently. These two analytical techniques are the Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT). Network optimization for the project is very important for the production of with "Aeta" brand Bottled Mineral Water produced by drinking water company in Madiun. This optimization is carried out in order to find out the production schedule of bottled water, there are 4 packages produced namely cups, 1.5 L bottles, 600 ml bottles, and gallons. After scheduling using the Critical Path Method, ie bottled water production will be more profitable if more products are in Gallon packaging. Because the Gallon packaging will save time this happens because the Gallon packaging does not go through cardboard packaging.